Why do resilient supply chains not always perform better? Evidence from Lebanese SMEs in a crisis-affected emerging economy - Khalil, Maya; El-Naga, Mohamed Abou; Shehata, Mohamed (Edelweiss Applied Science and Technology, 2026)
Despite its prominence in supply chain management research, supply chain resilience does not consistently deliver the performance benefits it is often assumed to generate. This study challenges the prevailing assumption that resilience is inherently performance-enhancing by empirically examining the conditions under which resilience contributes to organizational outcomes. Drawing on Dynamic Capabilities Theory and survey data from small and medium-sized enterprises (SMEs) operating in a crisis-affected emerging economy, the study investigates the interrelationships among supply chain resilience, sustainability, and performance. Using structural equation modeling (SEM), the findings reveal that resilience alone does not improve firm performance. Instead, its performance effects materialize only when resilience is deliberately translated into sustainability-oriented practices encompassing economic, environmental, and social dimensions. Supply chain sustainability is found to fully mediate the resilience–performance relationship, providing empirical evidence of a resilience–performance paradox. By reconceptualizing sustainability as a value-conversion mechanism rather than a complementary outcome, this study advances resilience theory beyond adaptive capacity and clarifies why resilience investments may fail to yield returns in volatile contexts. The findings offer critical insights for both scholars and practitioners by demonstrating that resilience without strategic sustainability integration risks becoming a costly capability rather than a source of sustained performance advantage, particularly for resource-constrained firms operating under persistent disruption.